2020
DOI: 10.5194/npg-27-175-2020
|View full text |Cite
|
Sign up to set email alerts
|

Study of the fractality in a magnetohydrodynamic shell model forced by solar wind fluctuations

Abstract: Abstract. The description of the relationship between interplanetary plasma and geomagnetic activity requires complex models. Drastically reducing the ambition of describing this detailed complex interaction and, if we are interested only in the fractality properties of the time series of its characteristic parameters, a magnetohydrodynamic (MHD) shell model forced using solar wind data might provide a possible novel approach. In this paper we study the relation between the activity of the magnetic energy diss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…A possible strategy in this direction would develop the Hamiltonian structure of dissipative plasma models; this is a matter that deserves future investigations. It may be interesting to extend in a future work the Parker dynamo waves recently obtained numerically in a standard MHD system [122] and different physical processes forced by solar wind fluctuations [123]. Moreover, the application of Noether's first and second theorems to explore conservation laws in NS-MHD and plasmas dynamics is essential.…”
Section: Discussionmentioning
confidence: 99%
“…A possible strategy in this direction would develop the Hamiltonian structure of dissipative plasma models; this is a matter that deserves future investigations. It may be interesting to extend in a future work the Parker dynamo waves recently obtained numerically in a standard MHD system [122] and different physical processes forced by solar wind fluctuations [123]. Moreover, the application of Noether's first and second theorems to explore conservation laws in NS-MHD and plasmas dynamics is essential.…”
Section: Discussionmentioning
confidence: 99%
“…In the last several decades, new strategies based on the study of complexity have been developed to study plasma systems. For instance, fractal and multifractal analyses have been carried out for turbulence in laboratory plasmas [ 3 , 4 ], geomagnetic activity [ 5 , 6 , 7 , 8 , 9 , 10 ], and solar wind dynamics [ 11 , 12 , 13 ]. From the perspective of self-organized criticality, sandpile models have been used to model the energy release from the Sun by means of solar flares [ 14 ] and geomagnetic activity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless the nature of the distribution function (thermal or non-thermal), plasmas show a self-organized critical behavior [ 28 ], allowing for the introduction of concepts from complex systems to study this criticality. Those methods are applied both in data sets and models [ 29 , 30 , 31 , 32 ]. Some authors have suggested that the change of fractals and multifractals indexes could be associated with dissipative events or related to the solar cycle, proposing a relation between multifractality and physical processes in plasmas, among them solar cycle, Sun–Earth system, or theoretical models of plasmas [ 29 , 33 ].…”
Section: Introductionmentioning
confidence: 99%